Report of a Working Group on Allium: Held in Tapioszele, Hungary, 29-31 March 1984 - United Nations Development Programme; International Board for Plant Genetic Resources; European Cooperative Programme for the Conservation and Exchange of Crop Genetic Resources (1984)
Report of the ECPGR Allium Working Group meeting, first meeting, 29-31 May 1984, Tapioszele, Hungary